Organotin (IV) Complexes And Their Biological Study With Azine/Schiff Base Ligands Containing NN/ON-Donor Atoms - Goh, Yee Han (Universiti Malaysia Sarawak, 2011)
Two ligands were synthesized, salicylaldehyde-benzophenone hydrazone ligand (1) contains ON-donor atoms; was synthesized by the condensation reaction of equimolar of salicylaldehyde and benzophenone hydrazone. On the other hand, 2-benzoylpyridinebenzophenone hydrazone ligand (2) contains NN-donor atoms; was synthesized by the condensation reaction of equimolar of 2-benzoylpyridine and benzophenine hydrazone. Organotin(IV) complexes of the two ligands (3-9) have been synthesized and characterized based on elemental analyses, molar conductance, electronic, FTIR and 1HNMR spectral studies. Organotin(IV) complexes (3-7) exhibited pentagonal geometry which have coordination number five (5) while organotin(IV) complexes (8-9) exhibited hexagonal geometry which have coordination number six (6). Ligand (1) and its organotin(IV) complexes (3,5-7) have also been tested for their toxicity against Artemia salina.